β-Caryophyllene Reduces the Inflammatory Phenotype of Periodontal Cells by Targeting CB2 Receptors - Giacomo Picciolo; Giovanni Pallio; Domenica Altavilla; Mario Vaccaro; Giacomo Oteri; Natasha Irrera; Francesco Squadrito (Biomedicines, 2020)
Human gingival fibroblasts (GF) and human oral mucosa epithelial cells (EC) with an inflammatory phenotype represent a valuable experimental paradigm to explore the curative activity of agents to be used in oral mucositis. The role of cannabinoid receptor 2 (CB2) has not yet been investigated in oral mucositis. The aim of this study was to evaluate the therapeutic potential of β-Caryophyllene (BCP), a CB2 agonist, in an in vitro model of oral mucositis. GF and EC were stimulated with LPS (2 µg/mL) alone or in combination with BCP; a group of LPS challenged GF and EC were treated with BCP and AM630, a CB2 antagonist. LPS increased the inflammatory cytokines TNF-α, IL-1β, IL-6 and IL-17A whereas it decreased the anti-inflammatory cytokine IL-13. The upstream signals were identified in an augmented expression of NF-κB and STAT-3 and in reduced mRNA levels of PPARγ and PGC-1α. BCP blunted the LPS-induced inflammatory phenotype and this effect was reverted by the CB2 antagonist AM630. These results suggest that CB2 receptors are an interesting target to develop innovative strategies for oral mucositis and point out that BCP exerts a marked curative effect in a preclinical model of oral mucositis which deserves to be confirmed in a clinical setting.